Worker well-being and public policy - Polachek, S. W. (Research in labor economics ;, 2003)
This volume contains 15 essays devoted to a number of multifaceted issues regarding how public policy affects worker well-being. Of the 15 chapters, the first two are the more general, dealing with overall earnings distribution and overall changes in welfare policy. The remaining chapters examine specific aspects of human welfare. They cover: fertility, disability, minimum wage, pension wealth, human capital investment, migration, health, and earnings. The book culminates with four chapters relating to gender and the family. Ultimately, determining who works, how much is earned, and how these earnings get distributed define the components of individual and social welfare. The topics covered in this volume shed light on these questions.